Dampak Testimoni terhadap Keputusan Berbelanja pada Pengguna Aplikasi Shope di Kota Mataram - Bukran, Bukran; Ramdani, Rizal; Irzani, Muhammad Andika Zainul (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This study examines the effect of testimonials on shopping decisions among Shopee app users in Mataram City. Utilizing a mixed-methods approach, the research integrates both quantitative and qualitative elements to enhance the understanding of the investigated issues. Quantitative methods involve performing t-tests and f-tests on a sample of 140 Shopee users in Mataram City. The results reveal that both testimonials concerning product quality and those regarding service quality are significant determinants of purchasing decisions. Specifically, testimonials related to product quality significantly influence purchasing decisions, as evidenced by a t-test value of 4.279, which exceeds the t-table value of 1.65589, thereby supporting H1. Similarly, testimonials regarding service quality also impact purchasing decisions, with a t-test value of 6.823 surpassing the t-table value of 1.65589, thus supporting H2. The f-test further confirms that testimonials about both product quality and service quality collectively affect purchasing decisions, with the significance value of 0.000 being less than the p-value of 0.05, thereby validating H3. Therefore, explanatory analysis underscores that testimonials can influence purchasing decisions due to the paramount importance of product quality assessments and service quality evaluations.